2020
DOI: 10.1007/978-3-030-45442-5_24
|View full text |Cite
|
Sign up to set email alerts
|

Text-Image-Video Summary Generation Using Joint Integer Linear Programming

Abstract: Automatically generating a summary for asynchronous data can help users to keep up with the rapid growth of multi-modal information on the Internet. However, the current multi-modal systems usually generate summaries composed of text and images. In this paper, we propose a novel research problem of text-image-video summary generation (TIVS). We first develop a multi-modal dataset containing text documents, images and videos. We then propose a novel joint integer linear programming multi-modal summarization (JI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…Learning process (LP): A lot of work has been done in both supervised learning [13,57,62,133,134] and unsupervised learning [25,26,[44][45][46]58]. It can be observed that a large fraction of supervised techniques adopt deep neural networks to tackle the problem [12,57,62,133], whereas in unsupervised techniques a large diversity of techniques have been adopted including deep neural networks [13], integer linear programming [44], differential evolution [45,46], submodular optimization [58] etc.…”
Section: On the Basis Of Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Learning process (LP): A lot of work has been done in both supervised learning [13,57,62,133,134] and unsupervised learning [25,26,[44][45][46]58]. It can be observed that a large fraction of supervised techniques adopt deep neural networks to tackle the problem [12,57,62,133], whereas in unsupervised techniques a large diversity of techniques have been adopted including deep neural networks [13], integer linear programming [44], differential evolution [45,46], submodular optimization [58] etc.…”
Section: On the Basis Of Methodsmentioning
confidence: 99%
“…Since a major focus of this survey is on MMS tasks with text as the central modality, the number of text documents in input can also be one way of categorizing the related works. Depending upon whether the textual input is single-document [13,57,133] or multi-document [44][45][46]58], the summarization strategies might differ.…”
Section: Kind Of Input Text (Kit)mentioning
confidence: 99%
See 3 more Smart Citations